Vegetation changes and sediment dynamics in the Lake Alaotra region, central Madagascar. (April 2023) - Broothaerts, Nils; Razanamahandry, Vao Fenotiana; Brosens, Liesa; Campforts, Benjamin; Jacobs, Liesbet; Razafimbelo, Tantely; Rafolisy, Tovonarivo; Verstraeten, Gert; Bouillon, Steven; Govers, Gerard
Madagascar is known for its high erosion rates in the central highlands, yet the role of human disturbance versus natural processes is not well understood and is a topic of ongoing debate. At present the necessary quantitative data to couple vegetation dynamics and sediment fluxes over time in Madagascar is scarce. This study aims to provide more insight in vegetation changes and sediment transfers over the last millennia in the Lake Alaotra region, and specifically on the role of human disturbances and natural processes. Our vegetation reconstruction is based on pollen records from two lake sediment cores, covering the last 2600 years. Sediment accumulation rates were calculated from cores obtained from the floodplains, from wetlands surrounding the lake, and from Lake Alaotra itself. Our data show an early opening in the landscape, between 2050 and 1700 cal a BP, with a transition from a wooded grassland or woodland/grassland mosaic towards open grassland and an increase in charcoal accumulation rates. (Indirect) human impact is suggested as the main driver for these vegetation changes. Floodplain and wetland sediment accumulation rates only increase in the last 1000 years and peak in the last 400 years. This increased accumulation can mainly be linked to the increased anthropogenic pressure (grazing and farming activities) that triggered increased lavaka (gullies) activity. No changes in accumulation rate were observed in Lake Alaotra, indicating that most sediments are buffered in the floodplains and wetlands. Overall, our pollen and charcoal data suggest an indirect effect of human disturbance on vegetation shifts whilst strong evidence was found for a direct effect of human disturbance on sediment accumulation through intensified use of the grasslands.